Phân tích thành nhân tử :
a) x4 - 2x3 + 2x2
b) x4 + 3x3 + 3x2 + x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: Ta có: \(x^2-4y^2-2x-4y\)
\(=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)\)
\(=\left(x+2y\right)\left(x-2y-2\right)\)
c: Ta có: \(x^3+2x^2y-x-2y\)
\(=x^2\left(x+2y\right)-\left(x+2y\right)\)
\(=\left(x+2y\right)\left(x-1\right)\left(x+1\right)\)
d: Ta có: \(3x^2-3y^2-2\cdot\left(x-y\right)^2\)
\(=3\left(x-y\right)\left(x+y\right)-2\cdot\left(x-y\right)^2\)
\(=\left(x-y\right)\left(3x+3y-2x+2y\right)\)
\(=\left(x-y\right)\left(x+5y\right)\)
e: Ta có: \(x^3-4x^2-9x+36\)
\(=x^2\left(x-4\right)-9\left(x-4\right)\)
\(=\left(x-4\right)\left(x-3\right)\left(x+3\right)\)
f: Ta có: \(x^2-y^2-2x-2y\)
\(=\left(x-y\right)\left(x+y\right)-2\left(x+y\right)\)
\(=\left(x+y\right)\left(x-y-2\right)\)
a) (x - y)(x + y + 3). b) (x + y - 2xy)(2 + y + 2xy).
c) x 2 (x + l)( x 3 - x 2 + 2). d) (x – 1 - y)[ ( x - 1 ) 2 + ( x - 1 ) y + y 2 ].
P(x) = 3x2 – 5 + x4 – 3x3 – x6 – 2x2 – x3
= – x6 + x4 + (– 3x3 – x3) + (3x2 – 2x2) – 5
= – x6 + x4 – 4x3 + x2 – 5.
= – 5+ x2 – 4x3 + x4 – x6
Và Q(x) = x3 + 2x5 – x4 + x2 – 2x3 + x –1
= 2x5 – x4 + (x3 – 2x3) + x2 + x –1
= 2x5 – x4 – x3 + x2 + x –1.
= –1+ x + x2 – x3 – x4 + 2x5
a.
$x^2-y^2-2x+2y=(x^2-y^2)-(2x-2y)=(x-y)(x+y)-2(x-y)=(x-y)(x+y-2)$
b.
$x^2(x-1)+16(1-x)=x^2(x-1)-16(x-1)=(x-1)(x^2-16)=(x-1)(x-4)(x+4)$
c.
$x^2+4x-y^2+4=(x^2+4x+4)-y^2=(x+2)^2-y^2=(x+2-y)(x+2+y)$
d.
$x^3-3x^2-3x+1=(x^3+1)-(3x^2+3x)=(x+1)(x^2-x+1)-3x(x+1)$
$=(x+1)(x^2-4x+1)$
e.
$x^4+4y^4=(x^2)^2+(2y^2)^2+2.x^2.2y^2-4x^2y^2$
$=(x^2+2y^2)^2-(2xy)^2=(x^2+2y^2-2xy)(x^2+2y^2+2xy)$
f.
$x^4-13x^2+36=(x^4-4x^2)-(9x^2-36)$
$=x^2(x^2-4)-9(x^2-4)=(x^2-9)(x^2-4)=(x-3)(x+3)(x-2)(x+2)$
g.
$(x^2+x)^2+4x^2+4x-12=(x^2+x)^2+4(x^2+x)-12$
$=(x^2+x)^2-2(x^2+x)+6(x^2+x)-12$
$=(x^2+x)(x^2+x-2)+6(x^2+x-2)=(x^2+x-2)(x^2+x+6)$
$=[x(x-1)+2(x-1)](x^2+x+6)=(x-1)(x+2)(x^2+x+6)$
h.
$x^6+2x^5+x^4-2x^3-2x^2+1$
$=(x^6+2x^5+x^4)-(2x^3+2x^2)+1$
$=(x^3+x^2)^2-2(x^3+x^2)+1=(x^3+x^2-1)^2$
x⁴ - 2x³ + 2x - 1
= (x⁴ - 1) - (2x³ - 2x)
= (x² - 1)(x² + 1) - 2x(x² - 1)
= (x² - 1)(x² + 1 - 2x)
= (x - 1)(x + 1)(x² - 2x + 1)
= (x - 1)(x + 1)(x - 1)²
= (x - 1)³(x + 1)
Ta có:
\(\left(x^4+2x^3-x-2\right)+\left(4x^2+4x+4\right)\)
\(=\left[\left(x^4+2x^3\right)-\left(x+2\right)\right]+4\left(x^2+x+1\right)\)
\(=\left[x^3\left(x+2\right)-\left(x-2\right)\right]+4\left(x^2+x+1\right)\)
\(=\left(x-1\right)\left(x+2\right)\left(x^2+x+1\right)+4\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left[\left(x-1\right)\left(x+2\right)+4\right]\)
\(=\left(x^2+x+1\right)\left(x^2+x+2\right)\)
\(x^4+2x^3-4x-4\)
\(=\left(x^2-2\right)\left(x^2+2\right)-2x\left(x^2-2\right)\)
\(=\left(x^2-2\right)\left(x^2-2x+2\right)\)
a) \(x^4-2x^3+2x^2\)
\(=x^2\left(x^2-2x+2\right)\)
b) \(x^4+3x^3+3x^2+x\)
\(=x\left(x^3+3x^2+3x+1\right)\)
\(=x\left(x+1\right)^3\)
\(x^4-2x^3+2x^2\)
\(=x^2.\left(x^2-2x+2\right)\)
\(=x^2.\left(x^2-x-x-1-1\right)\)
\(=x^2.\left[x.\left(x-1\right)-\left(x-1\right)-1\right]\)
\(=x^2.\left[\left(x-1\right)^2-1\right]\)